2018
DOI: 10.1093/rheumatology/key067
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap release is associated with antinuclear antibodies in systemic lupus erythematosus and anti-phospholipid syndrome

Abstract: Increased NET release is associated with autoimmunity and inflammation in SLE and APS. Inhibition of NET release thus could be of potential benefit in a subset of patients with SLE and APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 22 publications
3
51
1
1
Order By: Relevance
“…Importantly, neutrophil activation is related to inflammation, the formation of neutrophil extracellular traps and ANA increment. 49 However, we could not detect a reduction in neutrophil infiltration in kidneys (see Supplementary material, Fig. S8), suggesting a leading inflammatory context, which would be associated with a consequent increase of Treg cell number tending to reduce inflammation and damage.…”
Section: Discussionmentioning
confidence: 69%
“…Importantly, neutrophil activation is related to inflammation, the formation of neutrophil extracellular traps and ANA increment. 49 However, we could not detect a reduction in neutrophil infiltration in kidneys (see Supplementary material, Fig. S8), suggesting a leading inflammatory context, which would be associated with a consequent increase of Treg cell number tending to reduce inflammation and damage.…”
Section: Discussionmentioning
confidence: 69%
“…In clinical studies, we and others have demonstrated that excessive NET formation or impaired NET degradation is present both in patients with active AAV and in patients with severe SLE , and this is correlated with the severity of disease activity. Thus, preclinical and clinical studies have demonstrated an important role for NETs in the pathogenesis of both AAV and SLE.…”
Section: Introductionmentioning
confidence: 83%
“…The association of NETs with the autoimmune response in SLE and RA [8,9] might involve (i) the ineffective clearance of NETs contributing to the autoimmune response, (ii) the formation of neoepitopes due to modification of NET-associated proteins by neutrophil proteases and/or (iii) the formation of immune complexes when antibodies to NET components are already present, propagating the inflammatory process. Our data confirm the presence of anti-NET autoantibodies in SLE and RA sera, with a higher frequency in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with autoimmune diseases such as SLE and RA often have autoantibodies against NET components in their sera [8,9]. The immunogenicity of the NETs might be due in part be to generation of neoepitopes by neutrophil protease activities.…”
Section: Neutrophil Proteases Affect Autoepitopes On Netsmentioning
confidence: 99%
See 1 more Smart Citation